Dinamika Perubahan Kurikulum Terhadap Mutu Pendidikan di Indonesia - Fatimatuzzahroh . (Jurnal Kajian Anak (J-Sanak), 2022)
Curriculum changes are caused by several problems in curriculum implementation including the unpreparedness of students in implementing curriculum changes, limited facilities and infrastructure, lack of educational welfare, students do not participate in intense activities, and teachers are limited in mastering the new curriculum. The dynamics of curriculum change in Indonesia aims to make education in Indonesia able to compete with developed countries around the world. This study was conducted to determine the dynamics of curriculum changes on the quality of education in Indonesia. In its implementation, this study uses a qualitative research type. This research was conducted with a systematic literature review (SLR) research method which has an even and systematic nature by reviewing, analyzing and providing an assessment of the results of existing data, and the review process is carried out in thorough detail so that conclusions can be drawn. The results of this study indicate that curriculum changes occur due to a number of causal factors, including (1). The freedom of certain regions in the world from the domination of the colonialists. (2). The development of science and technology is very fast (3). Rapid growth with increasing population.